Socio-Cultural Analysis of Sport - Mazurkiewicz, Michał (Respectus Philologicus, 2015)
JARVIE, Grant, THORNTON, James, 2012. Sport, Culture and Society. An Introduction (second edition). London and New York: Routledge. p. 501. ISBN 978-0-415-48393-3